(untitled) (Journal of the College of Basic Education, 2023)
This research aims to know the impact of Daniel’s model on acquiring grammatical concepts among students of the College of Administration and Economics / University of Baghdad. In the control group, which was taught in the traditional way, and the study material was unified for the two groups, which are the grammar topics in the general Arabic language that are taught in the second course and include the grammar chapter, and the duration of the experiment was a full course. The researcher also prepared a tool for measurement, which is the concept acquisition test for the students (the research sample). 0.05) between the mean scores of the two groups and in favor of the experimental group that was studied using Daniel’s model.In the light of the foregoing, the researcher came up with a number of recommendations, including: Paying attention to the use of modern teaching models, especially the Daniel model. And the preparation of a pamphlet that includes modern teaching models to be distributed to teachers, and some suggestions, including: conducting a study similar to the current study in the Arabic language subject, and for different educational levels such as intermediate, preparatory and institutes, and conducting a study similar to the current study on males and females (comparative study).